(untitled) (Research, Society and Development, 2021)
New ready-to-use calcium silicate sealers (i.e., Bio-C Sealer and Sealer Plus BC) have proven to be bioactive and biocompatible materials. However, its antimicrobial activity has not yet been fully unraveled. The aim of this study was to evaluate the antimicrobial activity of bioceramic sealers (Bio-C Sealer, Sealer Plus BC and BioRoot RCS) in comparison with resin-based sealers (AH Plus, Sealer Plus and MTA Fillapex). Fresh sealers were tested against Enterococcus faecalis biofilms using direct and indirect contact tests. Colony forming units were counted after 24 hours. Additionally, crystal violet assay was used to evaluate the effects of sealer extracts on biofilm biomass. Optical density measurements were used to quantify biomass. Bioceramic sealers showed greater antimicrobial activity than resin-based sealers when in direct contact with biofilms (P < 0.05). Sealer Plus BC and Bio-C Sealer showed greater antimicrobial activity than AH Plus in the indirect test (P < 0.05), suggesting greater diffusion of these materials. The crystal violet test revealed that Sealer Plus BC was the most effective material in reducing the biofilm mass (P < 0.05) showing a significant difference with other bioceramic sealers. Bio-C Sealer and Sealer Plus BC showed greater antimicrobial activity than AH Plus against E. faecalis biofilms in direct and indirect tests. Furthermore, Sealer Plus BC showed the best effect on biofilm biomass.